STRATEGI PEMERINTAH KABUPATEN PAMEKASAN DALAM PEMELIHARAAN BAHASA MADURA - Mulyadi Mulyadi (IAIN MADURA, 2015)
This article is about to describe a research result on the study of language maintenance efforts planned by Pamekasan (a district in Madura island). This study is considered urgent due to a fact that Madurese (language spoken by Madura people) have been gradually left by the speakers. Three questions are purposed as the research focus, they are 1) how local government of Pamekasan use instructional field to maintain Madurese language; 2) how local government of Pamekasan use media to maintain Madurese language; and 3) how local government of Pamekasan use linguists to maintain Madurese language. This research is qualitative in design. The results show that the local government of Pamekasan put Madurese language as a subject in local schools that is mandatorily taught; it is also exclusively discussed in any formal forums about curriculum development; the local government also conducts in-house training programs for the Madurese language teachers.